Аналіз проектів представлених на містобудівельному конкурсі на створення концепції громадського центру району Сихів у м. Львові - Шуляр, Андрій (Видавництво Національного університету «Львівська політехніка», 2009)
There has been conducted a comparative analysis on town-planning competition of creating conception of community centre in Sykhiv district in Lviv. According to results of this competition it has been now investigating a process of introduction new types of dwellings with multiplicity community functions into a plan structure.
Keywords: містобудівельний; громадський; проект; Сихів; будівлі